A missing piece of the Papio puzzle: Gorongosa baboon phenostructure and intrageneric relationships. Issue 130 (May 2019) - Martinez, Felipe I.; Capelli, Cristian; Ferreira da Silva, Maria J.; Aldeias, Vera; Alemseged, Zeresenay; Archer, William; Bamford, Marion; Biro, Dora; Bobe, René; Braun, David R.; Habermann, Jörg M.; Lüdecke, Tina; et al.
Abstract: Most authors recognize six baboon species: hamadryas ( Papio hamadryas ), Guinea ( Papio papio ), olive ( Papio anubis ), yellow ( Papio cynocephalus ), chacma ( Papio ursinus ), and Kinda ( Papio kindae ). However, there is still debate regarding the taxonomic status, phylogenetic relationships, and the amount of gene flow occurring between species. Here, we present ongoing research on baboon morphological diversity in Gorongosa National Park (GNP), located in central Mozambique, south of the Zambezi River, at the southern end of the East African Rift System. The park exhibits outstanding ecological diversity and hosts more than 200 baboon troops. Gorongosa National Park baboons have previously been classified as chacma baboons ( P. ursinus ). In accordance with this, two mtDNA samples from the park have been placed in the same mtDNA clade as the northern chacma baboons. However, GNP baboons exhibit morphological features common in yellow baboons (e.g., yellow fur color), suggesting that parapatric gene flow between chacma and yellow baboons might have occurred in the past or could be ongoing. We investigated the phenostructure of the Gorongosa baboons using two approaches: 1) description of external phenotypic features, such as coloration and body size, and 2) 3D geometric morphometric analysis of 43 craniofacial landmarks on 11 specimens from Gorongosa compared to a pan-African sample of 352 baboons. The results show that Gorongosa baboons exhibit a mosaic of features shared with southern P. cynocephalus and P. ursinus griseipes . The GNP baboon phenotype fits within a geographic clinal pattern of replacing allotaxa. We put forward the hypothesis of either past and/or ongoing hybridization between the gray-footed chacma and southern yellow baboons in Gorongosa or an isolation-by-distance scenario in which the GNP baboons are geographically and morphologically intermediate. These two scenarios are not mutually exclusive. We highlight the potential of baboons as a useful model to understand speciation and hybridization in early human evolution.